From "What is Reading?" to What is Literacy?. Issue 3 (October 2016) - Frankel, Katherine K.; Becker, Bryce L. C.; Rowe, Marjorie W.; Pearson, P. David
In their 1985 report, Becoming a Nation of Readers: The Report of the Commission on Reading, Anderson, Hiebert, Scott, and Wilkinson defined reading and proposed five principles that guide its successful enactment: (1) reading is a constructive process, (2) reading must be fluent, (3) reading must be strategic, (4) reading requires motivation, and (5) reading is a continuously developing skill. In this article we revise the definition from reading to literacy and rethink the principles in response to theoretical and empirical developments in the intervening years with regard to the processes of, and contexts for, reading. Our updated principles include: (1) literacy is a constructive, integrative, and critical process situated in social practices; (2) fluent reading is shaped by language processes and contexts; (3) literacy is strategic and disciplinary; (4) literacy entails motivation and engagement; and (5) literacy is a continuously developing set of practices. We redefine each principle and offer new explanations in light of what we now know.